Prevalence of Thyroid Function Abnormalities and Its Association with Physical Fatigue in First-Year Medical Students - Ghosh, Arindam; Dasgupta, Debdeep; Biswas, Susumna (International Journal of Integrated Health Sciences, 2024)
Objective: To estimate prevalence and type of thyroid function abnormalities and explore their associations with physical fatigue in first-year medical students.Methods: This was a cross-sectional observational study comprising of 200 first-year medical students.  Demographic details and history of any significant medical illness was asked and noted. Thyroid function tests were conducted on all participants. The prevalence and type of thyroid function abnormalities were documented in all students,  and the presence and severity of physical fatigue were assessed on the basis of physical fatigue score. Participants with any kind of thyroid function abnormality were compared with those with normal thyroid function tests for presence and severity of fatigue.Results: Among the 200 students, 144 (72%) were males and 56 (28%) were females, resulting in a male-to-female ratio of 1:0.38. Subclinical hypothyroidism was identified in 9% of students (18 cases), while clinical hypothyroidism was present in 7% (14 cases). Additionally, subclinical hyperthyroidism was detected in 1% of students (2 cases), with no cases of clinical hyperthyroidism reported. Female students were found to be having more thyroid function abnormalities as compared to male students and the difference was found to be statistically significant (p=0.0109).  Students with abnormal thyroid function tests (34 cases) had a markedly higher mean FSS score (43.22±4.50) as compared to students with euthyroid (16.85±2.70).Conclusion: Subclinical thyroid abnormalities are prevalent among young individuals, particularly those with physical fatigue. This study revealed a significant link between presence of fatigue and the possibility of thyroid dysfunction.